Kinetic and Mechanistic Studies of Hydrolysis of 2-Ethyl-6-methylaniline Phosphate Tri-Ester in Acidic Medium - Tiwari, B.K.; Singh, Ruchi; Thakur, Dilip; Sharma, Garima; Chand, Shweta; Saxena, Amirta (Asian Journal of Chemistry, 2010)
Kinetic investigation of the hydrolysis of 2-ethyl-6-methylaniline phosphate tri-ester has been carried out in 0.1 to 6.0 mol dm-3 HCl and pH 1.24 to 7.46 at 97 ± 0.5 ºC in 30 % (v/v) aqueous dioxane mixture. Concentration of tri-ester in all kinetic runs was 5.0 × 10-4 mol dm-3. The rate of hydrolysis was determined by measuring the rate of appearance of inorganic phosphate by Allen’s modified colorimetric method. Pseudo first order rate coefficient have been calculated. Conjugate acid, neutral and mononegative species have been found to be reactive and contribute in over all rate. The rate coefficients estimated fairly in good agreement with the observed rates. Bond fission, molecularity and order of reaction have been suported by Arrhenius parameters, Zucker-Hammett hypothesis, concentration, solvent effect, etc. Comparative isokinetic rate data of similarly substituted other amino phosphate tri-ester, supported P–N bond fission.